PENGARUH PERBANDINGAN NENAS DENGAN BIT DAN KONSENTRASI GUM ARAB TERHADAP MUTU FRUIT LEATHER NENAS (The Effect of Ratio of Pineapple with Beet and Arabic Gum Concentrationon the Quality of Pineapple Fruit Leather) - Desintan Sri Mariati Sinaga; Ismed Suhaidi; Ridwansyah Ridwansyah (Universitas Sumatera Utara, 2017)
ABSTRACT The aim of this research was to find the effect of ratio of nanas with beet and several arabic gum concentration on the quality of mixture nanas and beet fruit leather. This research using completely randomized design with two factors, i.e : ratio of nanas with beet (90% : 10% ; 80% : 20% ; 70% : 30% ; 60% : 40%)and arabic gum concentration (0,50%, 0,75% and 1,00 ; 1,25%). Parameters analyzed were moisture content, ash content, vitamin C content, fiber content, total soluble solid (TSS) content, total acid content, score of organoleptic values of colour, taste and texture and hedonic of organoleptic values of colour, flavor, taste and texture. The results showed that the ratio of nanas with beet the had highly significant effect on moisture content, ash content, vitamin C content, fiber content, total soluble solid (TSS) content, total acid content, score of organoleptic values of colour, taste and texture, and hedonic of organoleptic values of colour, flavor, taste and texture. Arabic gum concentration had highly significant effect on moisture content, ash content, vitamin C content, fiber content, total acid. Interactions of the two factors had significant effect on moisture content, and had no significant effect on ash content, vitamin C content, fiber content, total soluble solid (TSS) content, total acid content, score of organoleptic values of colour, taste and texture, and hedonic of organoleptic values of colour, flavor, taste and texture. The ratio of nanas with beet of 90% : 10% and arabic gum concentration of 0,50% gave the best quality of fruit leather nanas. Keywords: arabic gum, beet, fruit leather, pineapple. ABSTRAK Penelitian ini bertujuan untuk mempelajari pengaruh perbandingan bubur buah nenas dengan bit dan konsentrasi gum arab terhadap mutu fruit leather nenas. Penelitian ini dilakukan dengan menggunakan Rancangan Acak Lengkap Faktorial dengan 2 faktor yaitu perbandingan bubur buah nenas dan bit terdiri dari 4 taraf yaitu (90% : 10% ; 80% : 20% ; 70% : 30% ; 60% : 40%) serta konsentrasi gum arab terdiri dari 4 taraf yaitu (0,50%, 0,75% and 1,00 ; 1,25%). Fruit leather yang dihasilkan diamati mutunya meliputi kadar air, kadar abu, kadar vitamin C, kadar serat kasar, padatan terlarut total, total asam, skor organoleptik warna, rasa, dan tekstur serta nilai hedonik warna, aroma, rasa,dan tekstur. Hasil penelitian menunjukkan perbandingan bubur buah nenas dan bit memberikan pengaruh sangat nyata terhadap kadar air, kadar abu, kadar vitamin C, kadar serat kasar, padatan terlarut total, total asam, skor organoleptik warna, rasa, dan tekstur serta nilai hedonik warna, aroma, rasa,dan tekstur. Konsentrasi gum arab memberikan pengaruh sangat nyata terhadap kadar air, kadar abu, kadar vitamin C, kadar serat kasar, dan total asam. Interaksi antara kedua faktor memberikan pengaruh nyata terhadap kadar air, dan memberikan pengaruh tidak nyata terhadap kadar abu, kadar vitamin C, kadar serat kasar, padatan terlarut total, total asam, skor organoleptik warna, rasa, dan tekstur serta nilai hedonik warna, aroma, rasa,dan tekstur. Perbandingan bubur buah nenas dan bit 90%:10% serta konsentrasi gum arab 0,50% menghasilkan fruit leather dengan mutu yang terbaik. Kata Kunci : gum arab, bit, fruit leather, nenas